The instrument development to measure the verbal ability of prospective high school students - Muhammad Rais Ridwan; Samsul Hadi; Jailani Jailani; Heri Retnawati (International Journal of Evaluation and Research in Education (IJERE), 2023)
An alternative for determining an accurate major for prospective high school students is not only based on academic scores but also on the results of the scholastic aptitude test (SAT). Verbal ability is an SAT subtest that assesses language management, vocabulary, and problem-solving abilities through a complete language study. This study developed a verbal ability test instrument for junior high school students consisting of the ability of synonyms, antonyms, and analogies. The data was collected from 300 junior high school students in grade nine who took a test with dichotomous data. The data analysis approach used one-order confirmatory factor analysis (CFA) with correlation factors. The results showed that CFA with correlation factors indicated the construct validity of the instrument was valid with the index criteria value =446.80, df=389, p-value=0.02267, root mean squared error of approximation (RMSEA)=0.022, goodness of fit index (GFI)=0.91, adjusted goodness-of-fit (AGFI)=0.89, and comparative fit index (CFI)=0.98. Then, construct reliability has good reliability with coefficient values for each dimension of 0.93, 0.95, and 0.84. As for the composite reliability of 0.88. It shows that using the verbal ability test instrument is feasible and has a reliable scale to measure the ability of junior high school students.